Efektivitas E-Participation dalam Mengawal Penegakan Hukum Pidana atas Kasus Kekerasan terhadap Aktivis Kontras Andrie Yunus - Siti Afra Aafiyah; Nasytha Muthiah; Nazwa Namira Putri Rusdiandi; Gendis Dewantari; Fatkhuri (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study aims to examine the impact of e-participation on law enforcement and the extent to which digital participation can promote substantive justice, focusing on the case of violence against KontraS activist Andrie Yunus. Furthermore, this study examines how public pressure through digital media can influence the response of law enforcement officials. The method applied in this study is a qualitative approach through literature analysis. Data were obtained from various journals, books, institutional reports, and media publications, which were then analyzed descriptively using a qualitative approach using the concept of e-participation and public sphere theory. The findings of this study indicate that e-participation can increase attention to a case and encourage an initial reaction from law enforcement officials through public pressure in the digital world. However, its effectiveness is inconsistent and does not always result in substantive justice. The phenomenon of "No Viral No Justice" reveals that law enforcement is influenced by public attention, which can lead to inequality. This research emphasizes that e-participation does not automatically strengthen democracy, but rather depends on the response of institutions and dynamics in the digital space. The results of this study deepen the understanding of digital democracy, particularly the relationship between public engagement and law enforcement.